A γ operational workspace for syntax in L1 and L2 processing: evidence from recursive re-representations of wh-fillers in French - Dekydtspotter, Laurent; Miller, A. Kate; Iverson, Mike; Cha, Jih-ho; Gilbert, Jane A.; Ahn, Jae Hyun; Meinert, Kent; Yang, Ludan; Zhang, Hongyu (Journal of neurolinguistics, 2025)
Recent theoretical proposals identify cortical gamma (γ) oscillations as signaling a mechanistic γ operational workspace (e.g., Murphy, 2024). Following the hypothesis that first (L1) and second (L2) languages involve shared neurofunctional mechanisms (Green & Abutalebi, 2008), we document cortical γ oscillatory dynamics in processing wh-filler-gap dependencies across a clause edge such as ‘Which decision regarding/about him did Paul say that Lydie had rejected without hesitation?’ in L1 and L2 French using electroencephalography. We manipulated wh-filler grammatical specifications with modifiers (Mods) vs. lexically specified complements (Comps) and with pronouns marked for antecedent gender or not. We used cluster-based non-parametric permutation tests (Oostenveld et al., 2011) in an analysis window covering ‘said that’ in two bins: 30–100Hz (broadband γ) and 30–50Hz (low γ). Event-related power differences (ERPDs) showed greater power for Comps than Mods and for antecedent-gender-specified than gender-unspecified Comps across L1 and L2. Narrowband/low-γ effects started in advance of bridge verb access and were maintained after verb access into the subordinator. These significant effects were echoed by broadband-γ ERPDs timed with the verb and subordinator, suggesting output activity in object creation. Two bursts of between-group ERPDs in low and broadband γ, respectively, reflected the (lack of) antecedent-gender specification of pronouns in anaphora relations. Hence, these patterns of oscillatory dynamics suggest that similarities and differences between L1 and L2 are accounted for by a γ-implemented operational workspace (Murphy, 2024) that enables the creation of structural and referential chain objects (Dekydtspotter et al., 2024). •A γ operational workspace enables basic syntactic and referential object creation.•γ-range oscillatory dynamics provide new insights into nature of L1 & L2 processing.•Neurofunctional bases of L1 & L2 processing reside in adaptive network dynamics.